First formal record of the incubating chiton Calloplax vivipara (Polyplacophora, Callistoplacidae) in Peru - Cardoso, Franz (2023)
Calloplax vivipara (Plate, 1899) is formal recorded for the first time in the southern Peruvian coast. Four specimens were found in rocky intertidal environment under blocks of stones in Islay, Arequipa, in December 2013 and October 2019. A female of 9.2 mm body length collected in the spring of 2013 presented six juveniles in the external part of the insertion zone of the ctenidia in the pallial groove, constituting the first case of an incubating chiton in Peru.